2017
DOI: 10.3389/fnagi.2017.00132
|View full text |Cite
|
Sign up to set email alerts
|

Blood Pressure Control in Aging Predicts Cerebral Atrophy Related to Small-Vessel White Matter Lesions

Abstract: Cerebral small-vessel damage manifests as white matter hyperintensities and cerebral atrophy on brain MRI and is associated with aging, cognitive decline and dementia. We sought to examine the interrelationship of these imaging biomarkers and the influence of hypertension in older individuals. We used a multivariate spatial covariance neuroimaging technique to localize the effects of white matter lesion load on regional gray matter volume and assessed the role of blood pressure control, age and education on th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
24
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 30 publications
(25 citation statements)
references
References 53 publications
1
24
0
Order By: Relevance
“…[ 5 ] WML refers to the entire spectrum of such lesions from mild perivascular tissue damage surrounding the lipohyalinotic arterioles which result in minimal axonal loss, to more severe ischemic damage, which can cause extensive myelin and axonal loss. [ 6 ]…”
Section: W Hite M Atter L mentioning
confidence: 99%
See 1 more Smart Citation
“…[ 5 ] WML refers to the entire spectrum of such lesions from mild perivascular tissue damage surrounding the lipohyalinotic arterioles which result in minimal axonal loss, to more severe ischemic damage, which can cause extensive myelin and axonal loss. [ 6 ]…”
Section: W Hite M Atter L mentioning
confidence: 99%
“…Moreover, WML-associated reductions in gray matter volume were significantly more substantial and executive function, and memory was worse in uncontrolled hypertensives than in normotensives. [ 6 ] In addition, cognitive decline was more associated with the degree of periventricular WML than that of subcortical WML. Intriguingly, the former may disrupt the long associative tracts that connect more distant cortical areas, whereas the latter may cause more limited damage to short cortico-cortical connections.…”
Section: W Hite M Atter L mentioning
confidence: 99%
“…Future work to obtain quantitative segmentation of deep vs. periventricular WMH volumes is warranted to help evaluate potential differences in their relation to brain aging. There is also growing interest in understanding how WMH volumes interact with gray matter in healthy aging and with cerebrovascular risk factors, like hypertension (e.g., Kern et al, 2017 ). Future studies using multimodal neuroimaging methods are needed to evaluate how associations between WMH volume and gray or WM integrity are altered by PSA in the context of healthy and pathological aging.…”
Section: Discussionmentioning
confidence: 99%
“…We observed that hypertension increases the risk of severity of white matter hyperintensities in the SWML group, but not in the PVH group. Longitudinal investigations revealed that well-controlled blood pressure in patients with hypertension significantly reduces the risk of severe white matter hyperintensity lesions [ 18 ]. Our results from the subjects who had taken antihypertensive treatment (85%) might support this speculation.…”
Section: Discussionmentioning
confidence: 99%